A Potassium Ion-Dependent RNA Structural Switch Regulates Human Pre-miRNA 92b Maturation. Issue 2 (19th February 2015) - Mirihana Arachchilage, Gayan; Dassanayake, Arosha C.; Basu, Soumitra
Summary: MicroRNAs (miRNAs) are an important set of oligonucleotide sequences with a biogenesis that involves Dicer-mediated cleavage as a critical step. Dicer cleaves the precursor miRNA (pre-miRNA) stem-loop structure to produce the mature miRNA. Using bioinformatics analysis, we discovered the presence of putative G-quadruplex (GQ)-forming sequences in about 16% of pre-miRNAs. We report the existence of a GQ as an alternative to the canonical stem-loop structure in the clinically important human pre-miRNA 92b. GQ formation led to unwinding of the stem-loop structure imparting resistance to Dicer-mediated cleavage both in vitro and in vivo. A potential K + ion-dependent equilibrium between GQ and the stem-loop structure has the ability to regulate the Dicer-mediated maturation of pre-miRNA 92b, which consequently affects target gene silencing. These findings unravel a new mechanism of regulation in pre-miRNA maturation, albeit at the RNA structure level. Graphical Abstract: Highlights: About 16% of human pre-miRNAs contain putative G-quadruplex (GQ) forming sequences Formation of GQ unwinds the canonical stem-loop structure of human pre-miRNA-92b GQ structure of pre-miRNA 92b coexists with stem loop in the presence of 100 mM K + GQ inhibits Dicer-mediated maturation of pre-miRNA 92b both in vitro and in vivo Abstract : G-quadruplex (GQ) structure regulates the maturation of human pre-miRNA 92b. Mirihana Arachchilage et al. describe the formation of GQ as an alternative to the canonical stem-loop structure and show that the GQ formation inhibits Dicer-mediated maturation of pre-miRNAs.